A critical investigation of managing the standards development process for the life insurance industry in Namibia - Kaimu, Himeesora Irene (Rhodes University, Faculty of Education, Department of Education, 2003)
The development of standards for education and training is regarded as a very important activity by many countries. Any country that sets standards for education and training is trying to define its training system and avoid duplication of training by providers who do not see eye to eye. National standards are public documents accessible to anyone interested in education and training. Namibia introduced standards setting as a core activity of administering the National Qualifications Framework in 1996 after the passing of the Namibia Qualifications Act by parliament. This research attempts to gain an understanding of how the process of developing standards for the Life Assurance Sector in Namibia was managed by focusing on the experiences of three persons who took part in the process of developing the said standards. The case study approach enabled me to gain considerable insight into management issues that may have influenced the process of developing these specific standards. The findings illuminate the management and leadership issues which characterised the process for the LA Industry. Several management issues emerge as key elements in the process. These include: A strong emphasis on transformational leadership through clear vision crafting; empowerment through emancipatory thinking; OD features such as problem solving and effective communication; the importance of organisational structure; the concept of a learning organisation and benchmarking as well as collegiality. This research explores the relationship between management thinking generally, and the management of the standards development process in particular.
Keywords: Life insurance -- Management -- Namibia; Insurance -- Namibia